The Study of Communication in Healthcare Organization - Wang, Jingyu (2017)
This research aims to find the problems and the reasons behind of the communication between healthcare providers and patients in China from the perspective of patients. Semi-structured interview with 7 interviewees was used to record and gather data in conversations. Findings of the interview indicate that there are three main problems and five main reasons behind. The problems are mainly about the doctors’ attitudes towards the patients, the deficient system and patients’ trust towards the healthcare providers. While the reasons behind are mainly of the unbalanced resource allocation of the healthcare providers, the social class, media, the knowledge gap and the expectations gap of the patients and reality. This research can contribute to the healthcare providers’ development strategy and training program for the co-workers especially the soft skill of communication.